Discovery of pyrogallol thermal reaction products from a model process of roasting coffee beans as potent α-glucosidase inhibitors. (April 2022) - Wang, Hui; Kang, Xiaoli; Sun, Shiwei; Yin, Yichen; Jiang, Kun; Tang, Guodong; Tang, Xinning; Wang, Wei
Abstract: The roasting process of pyrogallol, a polyphenol compound distributed in coffee beverages, significantly enhanced its α -glucosidase inhibitory activity. In this study, a bioassay-guided isolation of the thermal reaction products of pyrogallol led to the identification of two potent α -glucosidase inhibitors, 4-4′ dimer of pyrogallol (4, 4′-DP) and 4-5′ dimer of pyrogallol (4, 5′-DP). Their α -glucosidase inhibitory activity was higher than that of pyrogallol, as evidenced by comparing the IC50 values (206.2 ± 1.2  μ M for 4, 4′-DP, 187.6 ± 2.6  μ M for 4, 5′-DP, 2660 ± 60.1  μ M for pyrogallol). And the roasting products were more potent α -glucosidase inhibitors compared to acarbose (IC50  = 695 ± 12.7  μ M). Enzyme kinetics demonstrated that 4, 4′-DP and 4, 5′-DP inhibited α -glucosidase in an uncompetitive and a non-competitive manner, respectively. Docking simulations revealed that the main interaction forces between these two compounds and α -glucosidase were hydrogen bonding and hydrophobic effect. These results suggested that a simple roasting process might increase the α -glucosidase inhibitory activity of pyrogallol-containing foods such as coffee beverages. Graphical abstract: Image 1 Highlights: Pyrogallol exhibited potent α -glucosidase inhibitory activity after roasting. Two dimeric roasting products of pyrogallol were identified for the first time. Both products showed over 3 times stronger inhibition to α -glucosidase than acarbose. The products inhibited α -glucosidase in non-competitive and uncompetitive manners. Hydrogen bonding and hydrophobic effect were the main interaction forces.